Cytotoxicity and anti-herpes simplex virus type-1 activity of Kaempferia parviflora extract - Klinjan, Preeyaporn; Mungkornasawakul, Pitchaya; Tragoolpua, Yingmanee; Sangthong, Padchanee (Asia-Pacific Journal of Science and Technology, 2021)
Kaempferia parviflora is a medicinal plant in the family Zingibeaceae. Phytochemicals of K. parviflora have anti-inflammatory, anti-cancer, anti-bacterial, anti-oxidant, and anti-viral activities. Here, the anti-herpes simplex virus type-1 (anti-HSV-1) activity of K. parviflora extracts was determined in an in vitro model. The plant extracts were prepared from dried rhizomes using different extraction solvents such as methanol, ethanol, acetone, ethyl acetate, dichloromethane and hexane. For phylogenetic identification of K. parviflora nucleotide sequence analysis of K. parviflora showed 99.82% and 99.45% homology with reference sequences of K. parviflora in the GenBank database for trnL intron and trnL-F intergenic spacer, respectively. For phytochemical analysis, the hexane extract of K. parviflora revealed the highest amount of total polyphenols (153.39 μg of gallic acid equivalent (GAE)/g extract). The methanolic extract contained the highest flavonoid contents at 176.81 μg of auercintin (QE)/g extract. The cytotoxicities of the K. parviflora extracts were determined using 3-[4,5-dimethylthiazol-2-yl]-2,5 duphynyl tetrazolium bromide (MTT) assays. The methanolic extract showed low toxicity in the mouse fibroblast L929 cell line, with a 50% cytotoxic concentration (CC50) value of 25.27 ± 2.54 μg/mL. In addition, the hexane extract showed the lowest cytotoxic effect in Vero cells with a CC50 value of 41.77 ± 5.62 µg/mL. Regarding the anti-HSV-1 activity of K. parviflora extract, the ethanolic extract had the highest percentage of inhibition (52.57%) after 72 h of treatment at a concentration of 6.0 µg/mL; the 50% effective concentration (EC50) value and TI value of the ethanolic extract were 4.49 ± 1.00 and 6.59, respectively.